An Inconvenienced Youth? Ageism and its Potential Intergenerational Roots - North, Michael S. (2012)
Age is the only social category identifying subgroups that everyone may eventually join. Despite this, and despite the well-known growth of the older population, age-based prejudice remains an under-studied topic in social psychology. This paper systematically reviews the literature on ageism, highlighting extant research on its consequences and theoretical perspectives on its causes. We then identify a crucial gap in the literature: potential intergenerational tensions, speculating how a growing older population—and society’s efforts to accommodate it—might stoke intergenerational fires, particularly among the younger generation. Presenting both sides of this incipient issue, we review relevant empirical work that introduces reasons for both optimism and pessimism concerning intergenerational relations within an aging society. We conclude by suggesting future avenues for ageism research, emphasizing the importance of understanding forthcoming intergenerational dynamics for the benefit of the field and broader society.